« Brouillon du rapport présenté au concours pour accéder à la charge de directeur de promenades de la ville de Buenos Aires » dans Carlos Thays : ses écrits sur les jardins et les paysages - Charles Thays (Projets de Paysage)
Charles Thays is one of the French landscapers who practiced in Argentina in the nineteenth century. Heir to Edward Andrew, his originality relies to his adoption of the Argentinean identity and the quality of his work. In 1888, he was called in this country to achieve the current Sarmiento Park in Cordoba. In 1891, he won the competition to be Director of parks and walkways in Buenos Aires. He then draw the capital in the image of the Paris of Haussmann and Alphand in creating three parks : Febrero, Lezama and Colon ... He also fitted the neighborhoods of Palermo Chico, the constitución places, Congreso ... But this is only part of his creation that, far from stopping only to amenities and urban projects, is also about science. From 1902, he designs the Botanical Garden of Buenos Aires and the Iguazu Park, the Argentina’s first national park dedicated to the conservation of natural areas. Meanwhile, he has worked in all major cities in Latin America. By translating his submission for the competition of Director of Parks and Walkways in Buenos Aires, the article is a tribute to the historical culture of Charles Thays and aims to point out, how landscape project could benefit from this discipline field. We thank Sonia Berjman for allowing us to use her version of the text, she published and commented.